New cationic linear copolymers and hydrogels of N -vinyl caprolactam and N -acryloyl- N′ -ethyl piperazine : synthesis, reactivity, influence of external stimuli on the LCST and swelling properties - Deen, Gulam Roshan (2013)
New cationic linear copolymers of N-vinyl caprolactam (VCL) and N-acryloyl-N′-ethyl piperazine (AcrNEP) were synthesized by thermal free-radical solution polymerization in dioxane at 75 °C. The chemical composition of the copolymers was determined by 1H NMR spectroscopy. The copolymers were water-soluble at all composition and exhibited lower critical solution temperature (LCST) behavior. The LCST was greatly influenced by the AcrNEP content, changes in pH, temperature, salt and surfactant concentration of the external medium. The copolymers were rich in AcrNEP content due to its higher reactivity over VCL. The reactivity of AcrNEP and VCL were determined by the extended Kelen–Tüdös method to be r1AcrNEP = 0.41 and r2VCL = 0.13. The distribution of monomer sequence in the polymer chain was estimated using the terminal copolymerization model and the maximum tendency to alternation (70%) was at 45 mol % of AcrNEP in the feed. The effect of polymer concentration in the range 0.02 to 20 wt % on the LCST behavior showed a rather exponential decrease with the effect being more significant in the dilute regime. Simple inorganic salts such as sodium chloride and sodium bromide showed a salting-out effect while sodium iodide showed a salting-in effect of the copolymers in water. The salting-out coefficient of sodium chloride and sodium bromide evaluated by the Sestchenow equation was 1.37 and 1.12 L mol–1, respectively. The salting trend followed the order Cl– > Br– > I–. The intrinsic viscosity behavior and second-virial coefficient of the copolymers in water and in sodium chloride solution was studied in detail. Cross-linked cationic hydrogels of VCL and AcrNEP with a flexible (N,N′-methylenebisacrylamide) and stiff (1,4-diacryloyl piperazine) chemical cross-linker were prepared. The gels were responsive to pH and temperature changes of external medium. The influence of cross-linker type on the properties of the gels in terms of stimulus response, water transport mechanism, diffusion, and adsorption of an anionic dye (Congo red) were studied in detail.